Anxiety Levels of Severe COVID-19 Patients at Haji Adam Malik Hospital Medan in 2022 - Nurul Citta Banu Putri; Tarigan, Amira Permatasari; Pendiaman Pandia; Andika Pradana; Putri Chairani Eyanoer; Elmeida Effendy (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2023)
Background: The COVID-19 pandemic is affecting the healthcare system and causing psychological changes, not only among healthcare professionals but also among citizens. These psychological changes are caused by depression, fear, anxiety, or insecurity. This study aims to investigate the anxiety level of severe COVID-19 patients who were treated at Haji Adam Malik General Hospital Medan in 2022 Method: This research is a descriptive observational study at the Department of Pulmonology and Respiratory Medicine Haji Adam Malik Hospital Medan from January 2022 until several samples were fulfilled. Sampling was done by consecutive sampling technique by filling Google Form questionnaire. The HospitalÂ Anxiety and Depression Scale (HADS) questionnaire consists of seven items which can breakdown into anxiety subscales. The detail scores for every item ranged from zero to three. Score three indicated the highest level of anxiety. A total subscale score of >8 points out of 21 indicates significant anxiety symptoms. Data were analyzed descriptively to find out the frequency distribution of research subjects based on research sample characteristics. Results: From 36 research samples, 23 samples (63.9%) were male, and 13 samples (36.1%) were female. On anxiety levels, it was found that HADS-A scores were severe inÂ  21 patients with severe COVID-19 (58.3%) and moderate levels in 15 patients (41.7%) with severe anxiety levels. Conclusion: Anxiety levels appear to be significantly increased in patients with severe COVID-19